Gait differences between COPD and healthy controls: systematic review and meta-analysis - Joren Buekers; Laura Delgado-Ortiz; Dimitrios Megaritis; Ashley Polhemus; Sofie Breuls; Sara C. Buttery; Nikolaos Chynkiamis; Heleen Demeyer; Elena Gimeno-Santos; Emily Hume; Sarah Koch; Parris Williams; et al. (European Respiratory Review, 2024)
Background Despite the importance of gait as a determinant of falls, disability and mortality in older people, understanding of gait impairment in COPD is limited. This study aimed to identify differences in gait characteristics during supervised walking tests between people with COPD and healthy controls. Methods We searched 11 electronic databases, supplemented by Google Scholar searches and manual collation of references, in November 2019 and updated the search in July 2021. Record screening and information extraction were performed independently by one reviewer and checked for accuracy by a second. Meta-analyses were performed in studies not considered at a high risk of bias. Results Searches yielded 21 085 unique records, of which 25 were included in the systematic review (including 1015 people with COPD and 2229 healthy controls). Gait speed was assessed in 17 studies (usual speed: 12; fast speed: three; both speeds: two), step length in nine, step duration in seven, cadence in six, and step width in five. Five studies were considered at a high risk of bias. Low-quality evidence indicated that people with COPD walk more slowly than healthy controls at their usual speed (mean difference (MD) −19 cm·s−1, 95% CI −28 to −11 cm·s−1) and at a fast speed (MD −30 cm·s−1, 95% CI −47 to −13 cm·s−1). Alterations in other gait characteristics were not statistically significant. Conclusion Low-quality evidence shows that people with COPD walk more slowly than healthy controls, which could contribute to an increased falls risk. The evidence for alterations in spatial and temporal components of gait was inconclusive. Gait impairment appears to be an important but understudied area in COPD.